Truthful Equilibria in Dynamic Bayesian Games - Hörner, Johannes; Takahashi, Satoru; Vieille, Nicolas (Econometrica, 2015)
This paper characterizes an equilibrium payoff subset for Markovian games with private information as discounting vanishes. Monitoring might be imperfect, transitions depend on actions, types correlated or not, values private or interdependent. It focuses on equilibria in which players report their information truthfully. This characterization generalizes those for repeated games, and reduces to a collection of one-shot Bayesian games with transfers. With independent private values, the restriction to truthful equilibria is shown to be without loss, except for individual rationality; in the case of correlated types, results from static mechanism design can be applied, resulting in a folk theorem.